Endoparasites of rodents in two islands of the Straits of Malacca - S.N., Mohd Zain (Malaysian Journal of Science, 2008)
An endoparasitic survey of wild rodent populations of two islands, namely Pulau Langkawi and Pulau Jarak, was conducted to determine their biodiversity. Of the total of 13 rats captured, only one rat was trapped from Pulau Jarak. All rodents were identified and examined for endoparasites. These represented three commensal rodent species (Rattus tiomanicus, Rattus rattus diardii, and Rattus exulans), with R. tiomanicus being the most dominant species (84.3%) with the number of males (58.3%) captured being higher than females (41.7%). The rats were analyzed for parasite incidence, prevalence and intensity. The single rodent captured from Pulau Jarak was free from endoparasite infection. Post-mortem examination found high levels of endoparasitic infection in the hosts captured in Pulau Langkawi with the highest incidence in the small intestine, followed by caecum and stomach. Overall, the study showed high prevalence of multiple species of Heligmonellidae (100%) and only one cestode species (Rodentolepis nana). The endoparasite population was also found to be uniquely low in diversity. This study also showed that the present distribution of the rodent population in Langkawi is characteristic of a disturbed habitat and can be attributed to ongoing human activities in the surrounding area. This study provides a much needed baseline for the ecology of a disturbed island habitat. Further studies will shed light on the ecological interactions that influence the endoparasitic population of commensal rodents in the Langkawi archipelago. Kajian endoparasit tikus liar di dua pulau iaitu, Pulau Langkawi dan Pulau Jarak telah dijalankan untuk menentukan kepelbagaian spesis semasa. Sejumlah 13 tikus diperangkap dari kedua-dua pulau telah dikenalpasti dan dikaji untuk jangkitan endoparasitnya. Keputusan awal menunjukkan tiga spesis tikus komensal (Rattus tiomanicus, Rattus rattus diardii, dan Rattus exulans) diperangkap yang mana, R. tomanicus merupakan spesis paling dominan (83.3%). Bilangan tikus jantan (58.4%) yang diperangkap agak tinggi berbanding dengan betina (41.7%). Seterusnya, analisis data parasit populasi roden dikaji untuk kehadiran parasit, jangkitan kelaziman jangkitan dan intensiti jangkitan. Bedah siasat mendapati semua hos dijangkiti dengan bilangan endoparasit yang tinggi dalam usus kecil, diikuti dengan secum dan perut. Secara keseluruhan, kelaziman jangkitan tinggi ditunjukkan oleh spesis Heligmonellidae (100%) dan hanya satu spesis Cestoda (Rodentolepis nana). Jangkitan populasi endoparasit tikus didapati unik dengan kepelbagaian spesis yang rendah. Kajian ini juga jelas menunjukkan bahawa taburan populasi dalam habitat Pulau Langkawi ini terganggu dan dipercayai berkaitan dengan aktiviti manusia dipersekitaran. Kajian ini penting bagi menyediaan maklumat asas bagi ekologi habitat kepulauanyang terganggu. Kajian yang berterusan penting bagi menjelaskan interaksi ekologi yang mempengaruhi populasi tikus komensal di kepulauan Langkawi.